Educational interventions to improve detection and management of cognitive decline in primary care—An Italian multicenter pragmatic study - Lombardi, Gemma; Chipi, Elena; Arenella, Domenico; Fiorani, Ambra; Frisoni, Giovanni Battista; Linarello, Simona; Montanucci, Chiara; Muscio, Cristina; Pacifico, Irene; Pelizzari, Silvia; Perani, Daniela; Piras, Fabrizio; et al. (Frontiers in Psychiatry, 2022)
Timely detection of cognitive decline in primary care is essential to promote an appropriate care pathway and enhance the benefits of interventions. We present the results of a study aimed to evaluate the effectiveness of an educational intervention addressed to Italian family physicians (FPs) to improve timely detection and management of cognitive decline. We conducted a pre-post study in six Italian health authorities (HAs) involving 254 FPs and 3736 patients. We measured process and outcome indicators before the intervention (1 January 2014 to 31 December 2016) and after the intervention (1 January 2018 to 31 December 2019). One interactive face-to-face session workshop was delivered by local Cognitive Disorders and Dementia (CDCD) specialists and FP advisors at each HA, in the period September 2017-December 2017. The session focused on key messages of the local Diagnostic and Therapeutic Care Pathway (DTCP) or regional guidelines: a) the role of the FP for a timely suspicion of cognitive decline is fundamental; b) when cognitive decline is suspected, the role of the FP is active in the diagnostic work-up; c) FP’s knowledge on pharmacological and non-pharmacological interventions is essential to improve the management of patients with cognitive decline. An overall improvement in diagnostic procedures and management of patients with cognitive decline by FPs after the intervention was observed. The number of visits per year performed by FPs increased, and the time interval between the first FP consultation and the diagnosis was optimized. Neuroleptic use significantly decreased, whereas the use of benzodiazepines remained steadily high. Non-pharmacological interventions, or use of support services, were underrepresented even in the post-intervention. Differences among the participating HAs were identified and discussed. Results from this study suggest the success of the educational intervention addressed to FPs in improving early detection and management of cognitive decline, highlighting the importance to continue medical education in this field. At the same time, further initiatives of care pathway dissemination and implementation should promote strategies to enhance interactions between primary and secondary care optimizing the collaboration between FPs and specialists.